Towards a Decentred History of the Middle East: Transborder Spaces, Circulations, Frontier Effects and State Formation, 1920-1946 - (:unkn) unknown (My University, 2025)
Based on two epistemological notions – borderlands as histoire-problème (history-as-problem) on the one hand, and the co-production of borders between state and society (and ultimately the nation-state) on the other – our research project proposes to rethink the classical historical narrative about the emergence of the post-Ottoman Middle East. It takes its cue from transborder phenomena: on the one hand, the circulation of people, goods and ideas; and, on the other hand, the negotiation of ties between local actors and representatives of state authority. In so doing, the project departs from normative approaches about bordering processes and state sovereignty. Although it pays attention to issues such as international treaties and diplomatic negotiations over the delimitation of boundaries following the collapse of the Ottoman Empire, and thus draws on concerns formulated by the disciplines of International Law and International Relations, our history-based research agenda is mainly inspired by methodological and epistemological debates among geographers, anthropologists and sociologists.
Keywords: Borders; Middle East; Violence; Refugees; Mobility; Environment; Bedouins